Top Executive Rewards and Firm Performance: A Comparison of Japan and the United States - Kaplan, Steven N. (Journal of Political Economy, 1994)
This paper studies top executive turnover and compensation, and their relation to firm performance in the largest Japanese and U.S. companies. Japanese executive turnover and compensation are related to earnings, stock returns, and performance measures. The fortunes of Japanese top executives, therefore, are positively correlated with stock performance and current cash flows (or with factors contributing to such performance). The relations for the Japanese executives are generally economically and statistically similar to those for their U.S. counterparts. There is some evidence, however, that the fortunes of Japanese executives are more sensitive to low income but less sensitive to stock returns than those of U.S. executives. Copyright 1994 by University of Chicago Press.